2003
DOI: 10.1038/sj.bjc.6600703
|View full text |Cite
|
Sign up to set email alerts
|

On the biological relevance of MHC class II and B7 expression by tumour cells in melanoma metastases

Abstract: A large number of studies have indicated that specific immune reactivity plays a crucial role in the control of malignant melanoma. In this context, expression of MHC I, MHC II and B7 molecules by melanoma cells is seen as relevant for the immune response against the tumour. For a better understanding of the biological relevance of MHC II and B7 expression by tumour cells in metastatic melanoma, we studied the expression of these molecules in melanoma metastases in relation to the inflammatory response, regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 34 publications
2
39
0
1
Order By: Relevance
“…In a recent report, expression of B7.1 by tumor cells was found in 9 of 24 metastatic melanoma lesions. No significant correlation between B7.1 and tumor response to biochemotherapy, time to progression, or overall survival was found (28). The antitumor immune response by B7.1 and IL-12 in preclinical studies has been shown to be associated with a strong induction of IFN-g (18).…”
Section: Discussionmentioning
confidence: 96%
“…In a recent report, expression of B7.1 by tumor cells was found in 9 of 24 metastatic melanoma lesions. No significant correlation between B7.1 and tumor response to biochemotherapy, time to progression, or overall survival was found (28). The antitumor immune response by B7.1 and IL-12 in preclinical studies has been shown to be associated with a strong induction of IFN-g (18).…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, CD80 and CD86 expression has been found in a series cases of human melanoma in which low levels of RNA expression have been frequently documented (40,41). These findings, precisely in a human malignancy characterized by a certain degree of intrinsic immunogenicity, suggest that B7 family molecules could be involved in subverting routes of immune destruction of tumors.…”
Section: Cd25mentioning
confidence: 92%
“…The expression of low levels of CD80 and CD86 has been detected on an important fraction of human melanomas (40,41), myelomas (42), and acute myeloid leukemias (43). Moreover, low levels of expression of CD80 and CD86 detected by RT-PCR and surface staining has been reported in a series of cell lines derived from human carcinomas including some of colorectal origin (44).…”
mentioning
confidence: 99%
“…6A), the entire GFP sequence, from which the first methionine was changed for a valine, was cloned between the putative NH 2 -terminal signal sequence (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the last 70 residues from gp100 (residue 594 to the end). In pcDNA-gp/GFP+epit (presented in Fig.…”
Section: Robbins (Nci/nih)mentioning
confidence: 99%
“…Considering that f20% to 25% of melanomas naturally express MHC class II molecules during the process of malignant transformation (19), and perhaps >50% during inflammation and metastases formation (20,21), it is plausible that concomitant antigenic presentation by MHC class I and class II shapes antitumor responses mediating both positive and negative mechanisms. Thus, activation of tumor-specific CD8 + and CD4 + T cells may occur at the tumor site.…”
Section: Introductionmentioning
confidence: 99%